Day 3 Wed, November 09, 2016 2016
DOI: 10.2118/183052-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhance Energy Efficiency Through Advanced Process Control APC

Abstract: Advanced Process Control (APC) has been used extensively to assist in operating Gas Plants for increased reliability and profitability. But the constant increase in fuel, operating, and environmental costs, coupled with constant pressure to achieve higher efficiency levels from the existing facilities, has led to looking at APC applications for enhancing the energy efficiency. Process control of Acid Gas Removal units, Condensate Stabilizers, Utility sections, large Compressors/turbo generators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Results showed a remarkable increase in efficiency toward using the APC system. Also, Kumar et al examined the advantages of employing APC in Abu Dhabi gas industries as an essential strategy that increases reliability and profitability. It was found that the implementation of this technique would lead to a reduction in human error as well as economic and environmental benefits.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…Results showed a remarkable increase in efficiency toward using the APC system. Also, Kumar et al examined the advantages of employing APC in Abu Dhabi gas industries as an essential strategy that increases reliability and profitability. It was found that the implementation of this technique would lead to a reduction in human error as well as economic and environmental benefits.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…Prostate tumor development and progression in this model is akin to human prostate pathogenesis biochemically, pathologically and molecularly. 12 TRAMP mice are developed on a pure C57BL/6 background by prostate-specific expression of SV40 large T antigen using the rat probasin promoter. Mice were housed individually in a temperature maintained environment with food and water available ad libitum.…”
Section: Transgenic Mouse Modelmentioning
confidence: 99%
“…In process industries, demands for quality products with a lower rejection rate, minimal downtime, and safer operations are increasing. 1,2 Human errors cause approximately 70% of industrial accidents. 3 This may affect economics and environmental regulations.…”
Section: Introductionmentioning
confidence: 99%